Health choices and risk perception in elderly consumers: a systematic review. Issue 3 (3rd July 2022) - Guido, Gianluigi; Mileti, Antonio
Abstract: This paper provides a review of the marketing literature on elderly consumers' health choices and risk perceptions, in order to summarize the state of the art and provide a comparison term for future studies. The research was carried out on scientific articles published from 1970 up to 2019, in a selection of 100 thematic journals. The results confirmed the significance of health choices and risk perceptions as two essential points of marketing research concerning older consumers, and demonstrated that the growing needs and purchasing power of older consumers are accompanied by psychological, biological and relational conditions that can impact decision-making.